Upaya Pencegahan Kekurangan Energi Kronik (KEK) pada Remaja Putri di Smart Fast Global Education Jambi - Hatussaadah, Siti Fati; Rosalina, Elvin (Jurnal Abdimas Kesehatan (JAK), 2025)
Adolescents experience rapid growth and need good nutrition to support their growth and development. Adolescent girls who maintain their nutritional levels will maintain their reproductive health so that in the future they will become adult women who give birth to the next generation and gain adequate weight.  The aim of this activity is to increase the knowledge of educational participants about preventing CED in adolescent girls. CED is a condition where young women experience malnutrition (calories and protein) which lasts for a long time or is chronic, characterized by a LiLA proportion <23.5 cm, generally occurs in women of childbearing age which will have an impact on giving birth to LBW babies which will ultimately hinder the growth of children under five (stunting). This activity was carried out at Smart Fast Global Education Jambi, Jambi City for D1 students majoring in Hospitality, Aviation Commerce, AVSEC (Aviation Security) and Flight Attendants. The series of activities will start from September 2022 to February 2023, while education will be held on Friday, November 25 2022 at the Jambi Smart Fast Global Education Hall. There were 37 female students who attended, apart from that, 1 Smart Fast admin, 2 Bachelor of Nutrition Science students and the PkM Team attended. The time allocation is ± 90 minutes starting with the pretest, then delivering the material using power point, followed by a question and answer session, closing with the posttest. Before and after education, a pretest and posttest are given which are carried out by activity participants. There was a change in the average knowledge before and after being given education